AB1330 If remission and low disease activity is the treatment goal in rheumatoid arthritis, how far are we from this goal in patients currently treated with biologics in ordinary clinical practice? Data from the norwegian biorheuma project. (23rd January 2014) - Haugeberg, G.; Bader, L.; Hoff, M.; Haaland, K.; Gjesdal, C.; Storesund, B.; Gulseth, H.C.; Haavardsholm, E.; Mikkelsen, K.
Abstract : Background: Biologic agents are highly efficacious for treatment of rheumatoid arthritis (RA) (1). In 2010 recommendations from an international task force on treating RA to target (T2T) was published. (2) The chosen primary treatment target in RA was "a state of clinical remission which means the absence of signs and symptoms of significant inflammatory disease activity". In patients with long-standing disease low disease activity was considered as an acceptable alternative therapeutic goal. These guidelines proposed the use of validated composite measures to assess disease activity (e.g. DAS28, CDAI), which include joint assessments, in routine clinical practice to guide treatment decisions. Objectives: To examine disease activity and health status measures and examine the proportion of RA patients on biologics in low disease activity and remission in daily practice. Methods: Patients were recruited from rheumatology departments in Norway participating in the BIORHEUMA project (BIOlogic treatment of patients suffering from inflammatory RHEUMAtic disorders in Norway). The aim was 1. To implement the T2T recommendations in daily clinical practice by the use of a designated computerized system. 2. To obtain unselected real life data on clinical status and treatment practices in patients with inflammatory rheumatic joint disorders treated with biologics. All centers were using the GoTreatIT Rheuma software system (www.diagraphit.com ). Data collection included demographics, measures of disease activity (28 joint count, DAS28, CDAI) and health status (MHAQ, visual analogue scale (VAS 0-100 mm) measures for patient and doctor's global assessment, pain and fatigue) and laboratory data (ESR, CRP, RF and ACPA). Results: By the end of 2011 nine departments reported to have implemented the clinical standard of monitoring patients on biologics. Among these nine centers a total of 7206 RA patients (28.9% men, 71.1% women) had been registered in GoTreatIT Rheuma and 2745 were on biologics (27.4% men, 72.6% women). Mean (SD) age was 57.7 yrs and disease duration 13.8 yrs. Percentage of patients ACPA+ was 83%. 58.6% were on their first biologic, 23.7% were on their second, 10.9% on their third and 6.8% had been on more than 3 biologics. The following results were found: mean (SD) DAS28 3.17 (1.35), median [IQR] 28-swollen joint 1 [3], 28-tender joint 1 [4] and MHAQ 0.38 [0.62]. 38% were in remission (Das28<2.6) and 55% were either in remission or had low disease activity (DAS28 <3.2). Percentage of patients in remission and low disease activity was for those on first biologic 43.8% and 61.4%, second 35% and 50.7%, third 24.4% and 40.1%, or third or more 13.2% and 29.8%, respectively. Conclusions: In our Norwegian cohort of biologic treated RA patients more than 50% of patients had low disease activity or were in remission. References: Olsen NJ, Stein CM. New drugs for rheumatoid arthritis. N Engl J Med. 2004;350:2167-79. S molen JS et al. Ann Rheum Dis. 2010;69:631-7 Disclosure of Interest: G. Haugeberg Shareholder of: DiaGraphIT, Grant/Research support from: Roche, Pfizer, Abbott, L. Bader: None Declared, M. Hoff: None Declared, K. Haaland: None Declared, C. Gjesdal: None Declared, B. Storesund: None Declared, H. C. Gulseth: None Declared, E. Haavardsholm: None Declared, K. Mikkelsen: None Declared